Accelerated shelf-life study of fortified rice: evaluating micronutrient retention in different packaging options - Iftikhar, Mehreen (Kansas State University, 2022)
The number of people in the world affected by hunger continued to increase in 2020 under the shadow of the COVID-19 pandemic. After remaining virtually unchanged from 2014 to 2019, the prevalence of undernourishment (PoU) increased from 8.4 percent to around 9.9 percent between 2019 and 2020. Despite hunger, the biggest problem in developing countries is micronutrient deficiencies whereas in western countries the primary concern is obesity, but micronutrient deficiencies are also present here. In total around 2 billion people suffer from micronutrient deficiencies specially vitamin A, vitamin B, Folic acid, iron, and zinc. Fortification is considered as an effective strategy to address micronutrient deficiencies. Rice as a staple food used by more than half of the world. It contains mainly starch as other nutrients removed during milling process to produce white rice (Steiger et al 2014), considering wide acceptance worldwide rice has great potential to use effectively as carrier for fortificants for much needed micronutrients. My overall research was to analyze accuracy of measurement methods for micronutrient analysis, conduct accelerated shelf-life study on fortified rice produced using coating technology with different packaging at different temperature conditions and calculate overages of micronutrients needed to produce fortified kernels using extrusion technology. The first part of this study was to evaluate micronutrient contents in fortified rice produced using two different technologies (coating and extrusion), analyze effect of particle size during sample preparation on accuracy of results and compare different methodologies used by commercial labs for analysis of micronutrients in fortified rice. Different sample grinding methods were evaluated before the micronutrient analyses, and it was found that grinding leading to 95% of particles through 600 microns was optimal, and further intensity of grinding (example, 95% through 250 microns) did not lead to any improvement in results. Five different methodologies were used for the micronutrient analyses, coded as methods A, B, C, D and E, for the purpose of this study, based on standard protocols employed by various commercial testing labs. The maximum deviation from these standards for vitamin A in coated FRK was observed to be 127.7% (method B) and minimum 8.6% (method D); these maximum and minimum deviations were -63% (method C) and 6.7% (method E), respectively for extruded FRK. In general, the lowest deviations were observed for minerals (iron and zinc; in some cases, less than 1%) as opposed to vitamin concentrations. This study helped to understand the impact of FRK production method, sample preparation and analyses techniques on accuracy of micronutrient concentration measurements and would serve as basis for fortified rice suppliers and food aid organizations to improve quality and efficacy. The second part of this study focused on conducting accelerated shelf-life study. Fortified coated rice kernels (FRK) were mixed in a ratio of 1:100 with regular rice to produce fortified rice and packaged in woven poly propylene (WPP), laminated woven poly propylene (LWPP) and a new multi-layer hybrid bags (10 kg in size) and placed in 3 different accelerated storage conditions (27ºC, 33ºC and 43ºC at 60%RH) and key attributes micronutrient attributes (Vitamin A, Vitamin B1, Folic acid, Iron and Zinc) and microbial load (yeast and mold) were determined at regular intervals over a period of 6 months. Vitamin A was the most degraded micronutrient. Minerals results were relatively stable throughout the accelerated shelf-life period in all 3 packaging and storage conditions. Sensory results showed significant change in aroma in all 3 packaging and at the extreme storage condition (43ºC). Hybrid packaging bags were similar or better than other packaging options for retention of micronutrients and sensory attributes and minimizing microbial load in fortified rice. Data were fitted to the Arrhenius model to determine the rate constant. The third and final part of this study was to produce fortified rice kernels using extrusion technology. 4 formulations with different levels of micronutrients were used to produce fortified rice kernels. As per USDA recommendation vitamin A 500IU, vitamin B1 0.5mg, folic acid 0.13mg, Iron 4 mg and zinc 6 mg with 20 ± range should be present in final product. Keeping that standard in mind, our formulation (100% premix) gave best results. Overages more than that would exceed the acceptable level suggested by USDA, so 100% premix formulation is considered as optimum formulation and suggested to be used to produce extruded fortified kernels. Overall, this research has operational significance for food aid in general. Results will help in understanding gaps in current packaging and transition to new more effective packaging with optimum formulation suggestion to produce fortified rice kernels.
Keywords: Accelerated shelf life; Fortified rice; Packaging; Micronutrient retention; Vitamin A; Vitamin B1; Folic acid; Iron; Zinc; Arrhenius